Formulation and Evaluation of Physical Properties of Scrub Containing Kasumba Turate (Carthamus tinctorius Linn.) Water Extract - Salam, Putri Julyany; Mirawati, Mirawati; Purnamasari M, Vina (Universitas Muslim Indonesia, 2024)
The flowers of the kasumba turate (Carthamus tinctorius Linn.) has the potential as an antioxidant because it contains flavonoid compounds that can ward off free radicals. This study proposes and evaluates a pharmaceutically stable scrub from kasumba turate water extract. This study used an experimental method by extracting kasumba turate using an infusion method. The scrub formulation is made using a variety of emulgators, namely anionic emulgator amin soap (stearic acid and triethanolamine), nonionic emulgator (span 60 and tween 80) and anionic emulgator detergent (sodium lauryl sulfate). Physical stability tests were conducted before and after the condition accelerated for 10 cycles covering organoleptic, homogeneity, pH and viscosity. All scrub preparations that have been tested meet the criteria of each test both before and after the conditions accelerated, but the viscosity measurement results show that the formula using anionic emulgator amin soap is more stable physically, so it can be concluded that the water extract kasumba turate can be made into a stable scrub formula.